2016
DOI: 10.1126/scisignal.aaf2753
|View full text |Cite
|
Sign up to set email alerts
|

PERK mediates the IRES-dependent translational activation of mRNAs encoding angiogenic growth factors after ischemic stress

Abstract: Angiogenesis is induced by various conditions, including hypoxia. Although cap-dependent translation is globally inhibited during ischemia, the mRNAs encoding two important proangiogenic growth factors, vascular endothelial growth factor (VEGF) and fibroblast growth factor 2 (FGF-2), are translated at early time points in ischemic muscle. The translation of these mRNAs can occur through internal ribosome entry sites (IRESs), rather than through cap-dependent translation. Hypoxic conditions also induce the unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 41 publications
3
34
1
Order By: Relevance
“…The role of eIF2 has also been investigated for cellular internal initiation. Importantly, IRES-mediated mRNAs translation can operate upon global protein synthesis attenuation induced by eIF2 phosphorylation [116,[122][123][124][125][126][127]. In addition to the involvement of canonical initiation factors, efficient IRES-dependent translation requires auxiliary RNA-binding proteins, known as IRES trans-acting factors (ITAFs; Figure 2B) [128].…”
Section: Ires-dependent Translation Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of eIF2 has also been investigated for cellular internal initiation. Importantly, IRES-mediated mRNAs translation can operate upon global protein synthesis attenuation induced by eIF2 phosphorylation [116,[122][123][124][125][126][127]. In addition to the involvement of canonical initiation factors, efficient IRES-dependent translation requires auxiliary RNA-binding proteins, known as IRES trans-acting factors (ITAFs; Figure 2B) [128].…”
Section: Ires-dependent Translation Initiationmentioning
confidence: 99%
“…It was already demonstrated that VEGF-A, FGF-2 and DLL4 IRESs are activated upon stress conditions including hypoxia or ER stress and that these mRNAs remain efficiently translated under ER stress conditions despite phosphorylation of the major PERK substrate, eIF2α [123,124,142,168].…”
Section: The Angiogenesis Paradigmmentioning
confidence: 99%
“…Hence, mRNAs essential for cell survival and for stress response are translated via an IRES‐mediated mechanism . Cellular IRESs thereby allow cells to go through apoptosis, mitosis, or angiogenesis . Additionally, IRESs also aid in the translation of proteins encoded by mRNAs with highly structured 5′ UTRs, where the accessibility of the cap‐binding complex is limited (Fig ).…”
Section: Modes Of Translation Initiationmentioning
confidence: 99%
“…In eukaryotes, most translation initiation events rely on binding of the cap-binding complex at the 5' end of mRNA [30,31]. However, under the conditions of impaired canonical cap-dependent translation, cap-independent translation is required for cell survival and stress recovery [32][33][34]. During this process, 40S ribosomes can be directly recruited via an internal ribosome entry site (IRES) element to the 5' untranslated region (UTR) of mRNA [35,36].…”
Section: Bidirectional Translational Reprogrammingmentioning
confidence: 99%